Ostasienwissenschaften Meyer-Struckmann-Preis 2016: Florian Coulmas - Rosar, Ulrich (Reden zur Verleihung des Meyer-Struckmann-Preises durch die Philosophische Fakultät der Heinrich-Heine-Universität Düsseldorf, 2017)
The Meyer Struckmann Prize for Research in the Humanities and Social Sciences, awarded in 2016 for East Asian Studies, was awarded to Professor Dr Florian Coulmas. Florian Coulmas is Senior Professor of Language and Culture of Modern Japan at the Institute of East Asian Studies at the University of Duisburg-Essen. With Coulmas, the jury is honouring an academic who, as Director of the German Institute for Japanese Studies in Tokyo, has made a groundbreaking contribution to international research on demographic change in a non-Western industrial nation. According to the jury's assessment, the linguist, sociologist and Japanologist has an international reputation both through his professional expertise in the field of social science research on Japan and as a sociolinguist. In the German-speaking world, Coulmas has also made a name for himself as a popular non-fiction author on current Japanese topics.